(untitled) (Comprehensive Journal of Science, 2025)
Renewable energy from the sun is the energy that the sun radiates as light, which is subsequently used by people in a variety of ways, including photovoltaic cells. An endless supply of energy, like solar energy, is free since it is not owned by anyone. Under certain conditions, Maximum Power Point Tracking (MPPT) can be utilized to extract the maximum output that can be obtained from solar cells while also being linked into charge control systems. The specific input used in photovoltaic modules that has the capacity to produce the highest output power is known as the maximum power point, or highest voltage. Maximum power varies with the solar energy parameter that determines the photovoltaic (PV) module’s necessary temperature. MATLAB/SIMULINK is utilized to develop a Maximum Power Point Tracking (MPPT) strategy based on perturb and observe (P&O) method, which allows for the efficient operation of the photovoltaic system while accounting for the swift fluctuations in climatic circumstances. Based on simulation results, it was found that the point of operation oscillates around the maximum power point, as well as these oscillations are proportional to changes in incident illumination.